Educating in wartime: emotional impact and teaching challenges in humanistic training under armed conflict - Nataliia Sharata; Hanna Poberezhets; Tetiana Berezovska; Tetiana Kravchenko (Clío, 2025)
The primary objective of this study was to assess how forced conditions, particularly distance learning, impact the quality of education, students' emotional well-being, and academic performance. The survey was conducted between September 2022 and May 2023. The research methodology employed a mixed approach, incorporating both questionnaires and curriculum analysis. Teachers were asked about changes in teaching methods, adaptations of instructional materials, and strategies for supporting students during wartime. The key findings of the study indicate that the war has significantly disrupted the educational process, primarily due to technical issues such as power outages and unstable internet connections. These challenges have led to a decline in students' concentration and motivation. A notable difference was observed in the responses of male and female students. Female students were more likely to experience mental exhaustion, as they had to balance academic responsibilities with other obligations, whereas male students demonstrated greater adaptability but encountered difficulties related to military service. Teachers also reported an increased need to modify teaching materials and methods to provide emotional support for students. Quantitative analysis confirmed that female students experienced higher levels of stress during distance learning, while male students faced greater challenges due to their involvement in military service.